Quantum logic automata generalizing the edge of chaos in complex systems - Gunji, Yukio Pegio; Ohzawa, Yoshihiko; Tokuyama, Yuuki; Eto, Kentaro (Frontiers in Complex Systems, 2024)
While historically, researchers in the science of complex systems proposed the idea of the edge of chaos and/or self-organized criticality as the essential feature of complex organization, they were not able to generalize this concept. Complex organization is regarded at the edge of chaos between the order phase and the chaos phase and is regarded as a very rare case. Additionally, in cellular automata, the critical property is Class IV, which is also rarely found. Therefore, there can be overestimation for natural selection.More recently, developments in cognitive and brain science have led to the free energy principle based on Bayesian inference, while quantum cognition has been established to explain various cognitive phenomena. Since Bayesian inference results in the perspective of a steady state, it can be described in Boolean logic. In considering that quantum logic consists of multiple Boolean logic in terms of lattice theory, the perspective of the free energy principle is the perspective of order, and the perspective of quantum logic might be the perspective of multiple worlds, which is strongly relevant for the edge of chaos.